PENGOMPOSAN SAMPAH ORGANIK DAN ISOLASI BAKTERI TERMOFIL DARI KOMPOS [COMPOSTING ORGANIC WASTE AND ISOLATING THERMOPHILE BACTERIA FROM COMPOST] - Tjie Jan Tan; Juan Daniel; Hans Victor; Marcelia Sugata (Universitas Pelita Harapan, 2023)
Composting is one of the methods to sustainably minimize the accumulation of waste in the environment. Compost is made through the decomposition process of organic waste with the help of microorganisms. The process of making compost goes through several phases, one of the most important phases is the thermophilic phase. In this research, an evaluation was carried out on the effect of temperature, humidity, pH and aeration on the success of composting from leaves and twigs and braches of trembesi tree (Albizia saman). In addition, isolation and identification of thermophilic bacteria which play an important role in the composting process were carried out. Isolation of thermophilic bacteria is carried out when the compost making process is in the thermophilic phase. To support the growth of thermophilic bacteria, incubation during the isolation and purification process was carried out at a temperature of as high as 55-60 oC. Subsequently, thermophilic bacterial isolates were identified based on morphology and biochemical activity tests. The characterization results based on Bergey's Manual Systematic Bacteriology Second Edition Volume Three the Firmicutes indicated that the isolates obtained belonged to the genus Bacillus.Bahasa Indonesia Abstract:Pembuatan kompos merupakan salah satu cara yang dapat dilakukan untuk meminimalisasi penumpukan sampah di lingkungan secara berkelanjutan. Kompos dibuat melalui proses dekomposisi sampah organik dengan bantuan mikroorganisme. Proses pembuatan kompos melalui beberapa fase, salah satu fase terpenting adalah fase termofilik. Pada penelitian ini, dilakukan evaluasi pengaruh suhu, kelembapan, pH dan aerasi terhadap keberhasilan pembuatan kompos dari daun dan ranting serta dahan pohon trembesi (Albizia saman) Selain itu, dilakukan isolasi dan identifikasi bakteri termofilik yang berperan penting dalam proses pengomposan. Isolasi bakteri termofilik dilakukan saat proses pembuatan kompos berada pada fase termofilik. Untuk mendukung pertumbuhan bakteri termofil, inkubasi selama proses isolasi dan purifikasi dilakukan pada suhu 55-60 oC. Selanjutnya, isolat bakteri termofil diidentifikasi berdasarkan morfologi dan uji aktivitas biokimia. Hasil karakteriasasi yang dicocokan dengan Bergey’s Manual Systematic Bacteriology Second Edition Volume Three the Firmicutes mengindikasikan bahwa isolat yang diperoleh berasal dari genus Bacillus.